105k views
3 votes
HEY U, yea u please answer this I’m dumb and don’t understand also if u can please explain it xx

HEY U, yea u please answer this I’m dumb and don’t understand also if u can please-example-1
User Cositanto
by
4.8k points

2 Answers

6 votes

Answer:

7a+1

Explanation:

Since g(a)=3a and h(a)=4a+1 for (g+h)(a) you would do

first (3a)+(4+1)

second do like terms

7a +1

thers you got your anwer

User Noocyte
by
4.8k points
3 votes

Answer:

The answer is option D.

Explanation:

You have to add up both functions :

g(a) + h(a) = (g+h)(a)

(g+h)(a) = 3a + 4a + 1

(g+h)(a) = 7a + 1

User Houqp
by
5.1k points